INTEGRATING INTERCULTURAL COMMUNICATION COMPETENCE IN TEACHING ORAL COMMUNICATION SKILL - Irwandi Irwandi (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
This paper discusses the strategy of integrating the language learners’ intercultural communication competence in teaching oral communication skill. The idea emerges from the concept that English teaching and learning acquires a need to understand intercultural communication competence. An English language class that just focuses on grammar, syntax, phonetics, and some social conventions associated with the target language cannot contribute significantly into the learners’ insight on how people whose different culture communicate. Moreover, intercultural communication is more complex than communication between persons of the same culture. Thus, the practitioners of English language teaching need to know how to integrate the knowledge of intercultural communication in English language classes. However, there is no universally accepted strategy that can be applied by the instructors on how to integrate intercultural communication competence into the lessons at the classroom. This paper specifically proposes the strategy of integrating intercultural communicative competence in teaching English speaking skill. The strategy mostly encompasses activating learners’ cultural awareness, considering context, understanding obstacles to intercultural communication, understanding verbal and nonverbal issues, and designing classroom tasks for the intercultural competence. By including such strategy, the learners are guided not only in more successful communication, but also in constructing meaningful relationship with the target language speakers.